Bahasa Inggris - Kurniasih, Retno; Adawiyah, Wiwiek Rabiatul; Sudjadi, Achmad (Jurnal Akuntansi, Manajemen dan Ekonomi, 2024)
This study aims to identify factors that influence entrepreneurial intention among Generation Z, often referred to as "zillennials," within the college environment. Using a quantitative approach, this research examines the relationships between family support, entrepreneurial knowledge, entrepreneurial orientation, and entrepreneurial efficacy, and how these factors affect the intention to pursue entrepreneurship. Data were collected through a survey using questionnaires distributed to college students who met certain criteria. The sampling technique used was purposive sampling, with a total of 98 respondents. The analysis results show that all four independent variables—family support, entrepreneurial knowledge, entrepreneurial orientation, and entrepreneurial efficacy—significantly influence entrepreneurial intention. Family support was found to play an important role in motivating students to pursue entrepreneurship. Entrepreneurial knowledge helps individuals recognize business opportunities. Additionally, entrepreneurial orientation, which includes innovation and proactivity, also positively contributes to the intention to start a business. Entrepreneurial efficacy has been shown to boost students' confidence in facing business risks. This study highlights the importance of both internal and external factors in fostering entrepreneurial interest among young people. Colleges are encouraged to play a more active role in nurturing students' entrepreneurial spirit, helping them adapt to the increasingly competitive job market.